Mengurai Paradigma Pemidanaan Dalam Konteks Kebijakan Kriminal Di Era Digital - Dzalaqah, Farida; Sri Utari, Indah (Universitas Negeri Semarang, 2025)
The development of technology and information has created new spaces that offer convenience in life. However, behind this ease lies a loophole exploited by individuals with malicious intent. This space is used as a means to commit criminal acts. Crime in the digital era represents a modern type of offense that requires a different legal approach compared to conventional crimes. The shifting characteristics and modus operandi of criminal acts in the digital era must be met with a reconstruction of positive law in Indonesia. This is crucial to ensure that these crimes can still be effectively handled, thereby maintaining state order.